Spatial distribution characteristics and types of salt-affected soils spots developed on alluvial fan complex over old marine sediment, Thailand - Napaporn Phankamolsil; Kiattisak Sonsri; Irb Kheoruenromne; Robert J. Gilkes; Yutthana Phankamolsil (Agriculture and Natural Resources, 2021)
Salt-affected soils are universally known as one of the most important problematic soils causing a negative impact on agricultural lands worldwide. Thus, the aims of the current were: 1) to elucidate the spatial distribution of salt-affected soils, 2) to investigate the spatial factors impacting the distribution of salt-affected soils and 3) to classify the types of salt-affected soils. The study sites were located in Kamphaeng Saen district, Nakhon Pathom province, Thailand where the soils have developed under old marine sediment. Orthographic mapping was used to identify the locations of salt-affected soils; subsequently, 38 locations were selected. At these sites, soil samples were collected using a hand auger at four depths (0−20 cm, 30−50 cm, 60−80 cm, 80−120 cm) for analysis of their chemical properties. The ArcGIS software was used to analyze the spatial factors influencing the distribution of salts comprising the irrigation canal system, road construction, elevation and surface slope of the study area. The results indicated that the majority of salt-affected soils appeared where there was a salt crust, bare surface and halophytic plants were present, which all acted as environmental indicators. Generally, these soils were spatially distributed in the north of Kamphaeng Saen district, Nakhon Pathom province; the irrigation canal system, road construction and elevation may be regarded as the spatial factors leading to the occurrence of the salt-affected soils. Furthermore, these salt-affected soils were deep, moderately developed with possessing the ranges of ECe, SAR and ESP values from 0.20–74.70 dS/m, 2.30–85.09 and 2.74–113.23%, respectively. Thus, our finding indicated that the types of these salt-affected soils could be classified into two groups: 1) saline-sodic soils appearing at 34 study locations and 2) saline soils appearing at 4 study locations.